Estimation of parametric binary outcome models with degenerate pure choice-based data with application to Covid-19-positive tests from British Columbia - Nail Kashaev (The University of Western Ontario, Department of Economics, 2022)
I propose a generalized method of moments type procedure to estimate parametric binary choice models when the researcher only observes degenerate pure choices-based or presence-only data and has some information about the distribution of the covariates. This auxiliary information comes in the form of moments. I present an application based on the data on all COVID-19-positive tests from British Columbia. Publicly available demographic information on the population in British Columbia allows me to estimate the conditional probability of a person being COVID-19-positively tested conditional on demographics.
Keywords: C2; C81; I19; 330; Pure choice-based data; presence-only data; data combination; missing data; epidemiology; novel coronavirus